Beyond “Hybrid”. The Partially Misleading Relevance of a Notion, Alleged to Be One of Latour’s, and Its Possible Overcoming - Mattozzi, Alvise (E|C, 2023)
The present paper intends to show that “hybrid” is not a Latourian notion and, consequently, intends to explore what such claim entails for social research interested in the role artifact in our collectives. In the first part, it shows the marginal use of the notion of hybrid in Latour's work and questions the relevance Italian Greimasian semiotics of objects and design has given to it, by also proposing a hypothesis regarding the ground on which such attribution of relevance has emerged. In the second part, the paper explores alternatives to the notion of hybrid, able to account for the mediations carried out by individual aggregate actors a formulation replacing hybrid as well for those carried out by instances constituting individual aggregate actors. The second part of the paper, as well as the paper, ends by resorting to early Actor Network Theory's methodological proposal related to de scription which, founded on the semiotic method, is considered apt to properly address the issues raised by the notion of hybrid and by the debate around it.